PERAN KOMITMEN DAN DAYA DUKUNG ORGANISASIONAL PADA HUBUNGAN ANTARA KETIDAKPUASAN DENGAN KREATIVITAS KARYAWAN - Nugroho J. Setiadi; Agoestiana Boediprasetya; Nelavelly Virnanda Sudibyo (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
This empirical study examines the conceptual model of employee’s dissatisfaction to lead creative behavior. When employee feels that he/she has potentially to perform as a creative person, he/she will express their dissatisfaction through voice. Based on the exit-voice theory and empirical studies of organizational creativity (Zhou and George, 2003), this study identify two variables that potentially play a role on the relationship between job dissatisfaction and employee’ creativity, there are, continuance commitment and perceived organizational support. A number of hypotheses empirically to be proved. Interesting findings indicate that the perceived organizational support contribute on how individuals shape their job dissatisfaction led to creative behavior among employees in service organizations.